Yugas, Climate Cycles, and World Ages - Carlotto, Mark (Journal of Scientific Exploration, 2025)
Are the myths and legends of ancient cultures connected with human prehistory? Is there some underlying cycle, cosmic or other, behind the mythical ages of humanity? Motivated by correlations between sea-level rise at the end of the last ice age, flood myths, and other cataclysms, an analysis of global data sets reveals the presence of cycles roughly 6,000, 11,000 to 13,000, and 22,000 to 25,000 years in incident solar radiation (insolation) and global sea levels from the Middle to Late Pleistocene, and a 26,000-year periodicity in the timing of geomagnetic excursions over the past 100,000 years. 12,000-year cycles are the period of an ancient Vedic measure of time known as a mahayuga. It is shown that yuga cycles may be correlated with the timing of five hypothesized Earth crustal displacements over the last 130,000 years, and even longer periods of time defined in Vedic texts known as manvantara overlap human evolutionary timelines over the past 6-7 million years.